A sensitive HPLC-MS/MS screening method for the simultaneous detection of lupine, pea, and soy proteins in meat products. (January 2017) - Hoffmann, Björn; Münch, Siegfried; Schwägele, Fredi; Neusüß, Christian; Jira, Wolfgang
Abstract: The use of vegetable proteins in various types of meat products is common practice. In order to control food specifications, also with regard to food fraud and allergenic potential, a reliable detection of these additives is required. Here, a sensitive screening method for the simultaneous detection of lupine ( Lupinus angustifolius ), pea ( Pisum sativum ), and soy ( Glycine maxima ) in meat products applying High Performance Liquid Chromatography-Tandem Mass Spectrometry (HPLC-MS/MS) has been developed. After protein extraction and tryptic digestion, 3 to 4 marker peptides for each plant species were measured by HPLC-MS/MS. For matrix calibration, emulsion-type sausages with 0, 1, 6, 32, 160, 800, and 4000 mg/kg raw legume protein isolates/legume flour were produced. The mentioned legumes were detectable in sausages with concentrations of 6 mg/kg legume protein isolates/legume flour or greater. High correlation coefficients (R 2 > 0.999) between the peak areas of the mass transitions of the marker peptides and the contents of legume proteins in the meat products were obtained. The limits of detection (LODs) of the method were about 5 mg/kg meat product for pea protein, 4 mg/kg meat product for soy protein, and 2 mg/kg meat product for lupine protein. No false-positive or false-negative results were recorded. The applicability of the described method was tested by analyzing commercial meat products with and without added legume proteins. Highlights: Characteristic tryptic marker peptides for lupine, pea, and soy were identified. A simultaneous HPLC-MS/MS detection of these legumes in meat products is possible. Meat adulterations and traces of the allergens lupine and soy can be reliably detected. LODs in the low ppm range are comparable to ELISA and PCR methods.